2D cocrystal engineering: switching the robust carboxylic acid–pyridine supramolecular heterosynthon via an oriented external electric field. Issue 21 (11th May 2021) - Hong, Ye; Wang, Lu; Wang, Sheng-Fu; Wang, Dong; Chen, Ting
Abstract : The response of 2D cocrystals with the carboxylic acid–pyridine supramolecular heterosynthon to the oriented external electric field is identified on solid surfaces. Abstract : The cocrystal engineering strategy has been widely employed in the fabrication of functional organic structures and materials. In this respect, the supramolecular synthon concept exemplifies a retrosynthetic approach that may reduce the complexity and enhance the predictability of supramolecular synthesis. Here, we present the engineering of 2D cocrystals using an oriented external electric field (OEEF) based on the supramolecular synthon approach. By using scanning tunnelling microscopy (STM) and atomic force microscopy, the effect of the OEEF on the 2D supramolecular crystals bearing a carboxylic acid–pyridine heterosynthon is revealed at a molecular level. It is demonstrated that these 2D supramolecular cocrystals are formed on the surface in the absence of the external electric field. When an OEEF, i.e., a bias voltage in STM, is applied on the surface, the supramolecular cocrystals can be kept or disintegrate depending on the direction of the field. Efficient and reversible phase transition between the 2D supramolecular cocrystals and mono-component molecular assembly is induced by switching the polarity of the bias voltage. The response of the 2D supramolecular cocrystal to the bias voltage is explained by the influence of the OEEF on the carboxyl–pyridyl hydrogen bonding, which leads to the switching of the carboxylic acid–pyridine supramolecular heterosynthon. This work identifies the response of the 2D cocrystals with the carboxylic acid–pyridine supramolecular heterosynthon to the OEEF. It paves a way for rational design and construction of stimulus-responsive crystals and materials.